Gene expression, levels and polymorphism (Ala16Val) of mitochondrial superoxide dismutase in tuberculosis patients of Rajasthan - Gauba, Kavya; Gupta, Shruti; Shekhawat, Jyoti; Dutt, Naveen; Yadav, Dharmveer; Nag, Vijaya Lakshmi; Rao, Mahadev; Sharma, Praveen; Banerjee, Mithu (Microbes and infection, 2023)
Infectious diseases cause redox imbalance and oxidative stress (OS) in host. Superoxide Dismutases(SOD) decrease this OS. SOD2 gene polymorphism can influence the expression and levels of enzyme. To investigate the association of genetic polymorphism of MnSOD with enzyme levels and mRNA expression in TB patients. A total of 87 TB patients and 85 healthy individuals participated in the study. The serum SOD2 levels were measured by ELISA. Gene polymorphism was analysed using PCR-RFLP with BsaW1 as the restriction enzyme. Expression was studied by Real-TimePCR. Statistical significance was determined using the Mann–Whitney, Chi-square and Kruskal–Wallis tests and p value < 0.05 was considered statistically significant. The median(IQR) serum SOD2 levels of TB patients were lower than those of healthy subjects (4.64(6.48) vs 11.35(20.36)ng/mL respectively,p < 0.001). SOD2 expression was significantly down-regulated in TB patients with a fold change value of 0.312. The Val/Val genotype was higher in the patient group than healthy subjects (36.8% vs 23.5%). However, the difference observed between serum SOD2 levels and mRNA expression in the different genotypes were statistically non-significant. Significant difference was found between levels and expression of SOD2 in TB patients and healthy controls, but not for SOD2 gene polymorphism.